Congenital prepubic sinus presenting with abdominal pain: A case report - Mason Williams; Pamela Ellsworth; Abhishek Seth (Elsevier, 2023)
Introduction: Congenital prepubic sinuses are rare congenital anomalies of the urogenital tract with a varied presentation, but pain is an uncommon presenting symptom. Case presentation: This report describes a 14-year-old male who presented to the emergency department following five days of intermittent pain associated with a small opening superior to the base of the dorsum of the penis and superficial to the pubic symphysis. Surgical excision of the sinus tract revealed the sinus coursed towards the pubis and did not connect to the bladder. The histology of the tract revealed transitional epithelium surrounded by smooth muscle. Conclusion: Management of congenital prepubic sinuses relies upon prompt recognition, diagnosis, and surgical intervention to prevent complications.